Keadilan Substantif Dalam Proses Asset Recovery Hasil Tindak Pidana Korupsi - Ade Mahmud; Chepi Ali Firman Z; Husni Syawali; Rizki Amrulloh; Weganisa (Jurnal Suara Hukum, 2021)
The problem of returning assets in cases of corruption act still displays the face of procedural justice and is far from substantive justice, because the value of state losses in many cases are not returned in full and the perpetrator is punished with minor crimes. This study uses a normative juridical approach using secondary data which is analyzed qualitatively because it does not use mathematical formulas and numbers. The urgency of returning assets resulting from criminal acts of corruption is based on the reasons for preventing assets from being used to commit other crimes in the future, the reasonableness that morally the perpetrators of the crime do not deserve to control assets illegally acquired, the priority reasons are based on the valuation of assets controlled by the perpetrator. social rights and reasons of ownership that the state has an interest in taking assets controlled by the perpetrator against the law. The progressive legal model for expropriation of asset recovery takes the form of (a) tracing assets and freezing and confiscating assets of the perpetrator regardless of whether or not they are related to the criminal act of corruption. (b) the application of the burden of proof is reversed. (c) the judge imposes a verdict in the form of a penalty of substitute money without being subject to imprisonment, this decision is based on a guarantee for repayment of replacement money for the assets that have been confiscated. Keywords: Substantive Justice, Asset Recovery. Corruption.